Pemanfaatan chatbot untuk informasi pendaftaran calon mahasiswa baru di perguruan tinggi - Fitria, Ria; Tulodo, Rizki Prasetyo; Sofyan, Ali (Fakultas Teknologi Informasi, Universitas Kristen Satya Wacana, 2025)
A good administrative system in admitting new students not only makes things easier for prospective students, but also increases the efficiency and effectiveness of the registration process. With a structured system, prospective students can register directly at the counter or via an online platform, which makes access easier and reduces waiting time1. This is in line with the need for institutions to adapt to the digital era and improve services to prospective students. However, this often happens in the process of accessing information and inputting data. Because some students are still searching for registration information at Pancasakti University manually, this will take time and energy. When Pancasakti University Tegal opened student registration, thousands of prospective Pancasakti University Tegal students and their parents contacted the administration of Pancasakti University Tegal with various questions about the registration process and requirements. Chatbots, as a technological innovation based on artificial intelligence, offer an efficient solution to this problem. Chatbot is AI software that can interact with humans via text or voice, simulate human conversation, and provide relevant responses..